Immunotherapy in colorectal cancer: for the select few or all? - Arora, Sukeshi Patel; Mahalingam, Devalingam (Journal of Gastrointestinal Oncology; Vol 9, No 1 (February 08, 2018): Journal of Gastrointestinal Oncology (Evolving Role of Immune-oncology Therapeutics in GI Malignancies), 2017)
Over the past few years, the role of immunotherapy in colorectal cancer (CRC) has expanded, specifically in subsets of CRC with microsatellite instability (MSI) for which newer agents, such as programmed death-1 (PD-1) inhibitors, are efficacious. While other immunotherapeutic agents are more immature in development, they have the potential to enhance the efficacy of PD-1 inhibitors and play a role in the treatment algorithm for all subsets of CRC patients. In this review, we will discuss immunotherapeutic agents in development in patients with CRC. We will review the later phase studies that elucidate the role of immunotherapy in CRC and provide hope for changing the treatment paradigm for CRC in the future.